Effect of Moist and the Depth of Water Leak Layer in Building on Capacitance of Coplanar Moist Detector - Younes, Mouin (Latakia University Journal -Engineering Sciences Series, 2019)
Capacitors consisting of electrodes in the form of coplanar metal plates fixed on a substrate are widely used in engineering for measuring, in particular as primary measuring transducer of humidity and moisture meters at the high-frequency. Capacitors used as water-leakage detectors for such purposes are made, as a rule, in the form of a flat dielectric rectangular base with coplanar electrodes of equal width and uniformly spaced, imbedded into it. Conformal mapping method is used to calculate the capacitance of rectangular capacitors with two plates over multi layer materials. The calculating the capacitance of such capacitors with finite dimensions of plates is presented here. The method proposed here makes it possible to apply the design equations to rectangular printed capacitors in order to calculate the variation of their capacitance by Variation characteristic of the imbedded layer because of the water leak. المكثفات المصنعة على شكل صفيحتين معدنيتين فوق طبقة من الأساس واقعتين في مستوٍ واحد تستعمل استعمالاً واسعاً في هندسة القياسات بوصفها مبدلات قياس أولية في مقاييس رطوبة الهواء و رطوبة المواد الصلبة عند الترددات العالية. الشكل المكثفي المدروس المراد استعماله كاشفاً لتسرب المياه مصنع على شكل دارة مطبوعة مكونة من قطبين متماثلين في مستوٍ واحد يفصل بينهما فراغ متجانس ومتوضعة على طبقة أساس . تستعمل نظرية التخطيط التطابقي (Conformal mapping) لحساب السـعة C للوحين معدنيـين يقعان في مستوٍ واحد(Two coplanar Plates) متوضعان فوق طبقات من مواد مختلفة الخواص الكهربائية (لها ثوابت عزل نسبية وناقليات نوعية مختلفة). وقد تم استعراض طريقة حساب السعة لمثل هذه المكثفات ذات الألواح محدودة الأبعاد. تمكننا الطريقة المدروسة من تطبيق معادلات التصميم للمكثفات المطبوعة مستطيلة الشكل، وذلك لحساب تغير السعة للشكل المدروس المستعمل كاشف رطوبة (Detector) عند تغير خواص الطبقات التي يتوضع عليها نتيجة تسرب المياه إلى داخلها . Capacitors consisting of electrodes in the form of coplanar metal plates fixed on a substrate are widely used in engineering for measuring, in particular as primary measuring transducer of humidity and moisture meters at the high-frequency. Capacitors used as water-leakage detectors for such purposes are made, as a rule, in the form of a flat dielectric rectangular base with coplanar electrodes of equal width and uniformly spaced, imbedded into it. Conformal mapping method is used to calculate the capacitance of rectangular capacitors with two plates over multi layer materials. The calculating the capacitance of such capacitors with finite dimensions of plates is presented here. The method proposed here makes it possible to apply the design equations to rectangular printed capacitors in order to calculate the variation of their capacitance by Variation characteristic of the imbedded layer because of the water leak.